Concept and rationale of evolutionary plant breeding and its status in Nepal - Joshi, B. K.; Ayer, D. K.; Gauchan, D.; Jarvis, D. (Journal of Agriculture and Forestry University, 2020)
Nepal has released and registered a total of 623 genetically uniform (mono genotyped) varieties. These varieties were developed by both conventional and classical plant breeding, biotech-assisted plant breeding, and participatory plant breeding methods. However, these varieties have been shown to vary in their yield performance over the years and locations. Smallholder farmers dominate agriculture with 53% of the land-owning households with their land holding size of less than 0.5 ha in Nepal. Farmers are increasingly losing their own saved seeds. There have been impacts of weather variability, often modern crop varieties are not available to suit with these changing conditions. Farmers are looking for crop varieties that can better adapt to these changing conditions, and seeds of which can be saved for the next season planting. Evolutionary Plant Breeding (EPB), which creates and maintains a high degree of genetic diversity (i.e. polymorphic population), is a choice for breeders and farmers for accelerating the development of climate resilient and sustainably high-performance crop varieties. In 2015, the National Gene Bank in Nepal started an EPB program for the local rice variety, Jumli Marshi with the objective of enhancing genetic conservation through creating a dynamic gene pool. An evolutionary population can be compared to a living gene bank, not only in line with bringing greater yield stability, but also greater diversity in aroma, nutritional value and quality. Evolutionary populations have the potential to produce higher yields and perform better than their local or improved counterparts in adverse, or stress conditions. Under stress conditions, evolutionary populations have also been shown to be more resistant to weeds, diseases and pests damage than homogenous crop populations. Based on the source of diversity used in EPB, two different types of populations- Composite Cross population, and Composite Mixtures, population are developed. With the exception of Europe, and only for some crops, existing seed policies do not favor such populations. Therefore, there is a need to revise seed regulations in order to allow the cultivation of a higher degree of genetic diversity.